Association between Metabolic Syndrome Components and Sudden Sensorineural Hearing Loss - Al Ciptaning Laras; Ray W. Basrowi (ILUNI MKK FKUI and PRODI MKK FKUI, 2023)
Introduction: Sudden sensorineural hearing loss (SSNHL) is a common form of hearing loss, and has been associated with several inflammatory diseases, which are known to cause vascular and neurological problems. Metabolic syndrome, whose main components are diabetes mellitus and dyslipidaemia, is considered a chronic inflammatory disease. Since both medical conditions share common aetiology, this literature review aims to examine the potential correlation/association between SSNHL and metabolic syndrome and the prognosis by analysing electronic databases.Methods: A literature review which systematically searched relevant studies from four internet databases: PubMed, Scopus, Google Scholar and the Cochrane. The studies searched were limited to original studies submitted between year 2011 and 2023, covering randomized controlled trial, case control, cohort, or cross sectional, analysing 1) the prevalence of Metabolic syndrome among SSNHL patients, and/or 2) the rate of recovery and prognosis of SSNHL patients who had metabolic syndrome. Results: Sixteen observational studies have been examined and reviewed. Twelve of these studies analysed the correlation between the metabolic syndrome and its components and SSNHL, and they demonstrated that risk of having SSNHL increases for patients who were diagnosed with components of metabolic syndrome. One of the studies claimed that people with metabolic syndrome have 3.54-fold increased risk of having SSNHL (P < .001). Nine of these studies analysed the correlations between metabolic syndrome and recovery rate of patients diagnosed with SSNHL. All 9 studies showed that metabolic syndrome negatively influenced the recovery rates of patients diagnosed with SSNHL, with one of the studies demonstrated that the likelihood of being unresponsive to treatment was higher in those with metabolic syndrome, with odds ratio of 2.18 (P < .001). Conclusion: Our findings suggest positive association between prevalence of SSNHL and metabolic syndrome; the risk of having SSNHL increases for patients who were diagnosed with components of metabolic syndrome. Our findings also suggest that SSNHL patients who are also diagnosed with metabolic syndrome have worse recovery rate and poorer prognosis.